Fabrication and Testing of Plastic Interlocking Pavements (PIP) - Khamsani, Muhamad Fatih; Mohd Zamri, Muhamad Ammar Danial; Mohd Talha, Muhammad Faiz; Abd Kadir, Aslila (Multidisciplinary Applied Research and Innovation, 2025)
The utilization of waste materials in building has attracted substantial attention in recent years due to its potential for sustainable and eco-friendly. This study investigates the practicality of using sand plastic, a composite material made from waste plastic and sand aggregates, in the manufacturing of pavers. The aim was to evaluate the mechanical characteristics and appropriateness of sand plastic pavers for diverse uses in building and landscaping. The experimental study entailed the creation of mixes consisting of sand and waste plastic, with different ratios of plastic to sand which is 20%, 25% and 30%. The load-bearing capacity of the generated paver samples was evaluated by conducting compressive strength tests according to standard protocols. In addition, the material’s performance under various situations was evaluated by examining its water absorption, flexural strength, and durability characteristics. The findings indicated that the use of waste plastic in the form of sand plastic composites resulted in paver samples exhibiting favourable mechanical characteristics. The compressive strength of the sand plastic pavers demonstrated comparable values to those of conventional concrete pavers. Furthermore, the water absorption properties and durability performance indicate that these pavers have the potential to be suitable for outdoor use. This study highlights the capacity of sand plastic to serve as a sustainable substitute material for making pavers. It helps control waste by utilising abandoned plastic and offers a practical solution for improving the mechanical and environmental characteristics of construction materials. The findings provide valuable insights into the practicality of utilising sand plastic technology for creating long-lasting, environmentally friendly pavers that are appropriate for a wide range of construction and landscape application